Female labor market transitions in Europe - Lutz C. Kaiser (Institute for the Study of Labor (IZA), 2006)
Using micro panel data, labor market transitions are analyzed for the EU-member states by cumulative year-by-year transition probabilities. As female (non-)employment patterns changed more dramatically than male employment in past decades, the analyses mainly refer to female labor supply. In search for important determinants of these transitions, six EU-countries with different labor market-regimes are selected as examples (Denmark, Germany, Netherlands, Portugal, Ireland, UK). Within these countries, women's determinants of labor market transitions are compared by means of pooled multinominal logit-regressions. The outcomes hint at both, the importance of socio-economic determinants, like the life cycle or human capital, but also address gender related differences in the paths of labor market transitions. Clearly, the observed cross-national differences are driven by specific national institutional settings. Among others, one of the most crucial features is the day-care infrastructure concerning children, which either fosters or restricts a sustainable risk management between family and work in the respective countries.
Keywords: J21; J22; J78; 330; labor supply; labor market transitions; socio-economic determinants; institutional settings; risk management; cross-national comparison